Integration, Community, and the Medical Model of Social Injustice. Issue 2 (27th February 2019) - Madva, Alex
Abstract: I defend an empirically‐oriented approach to the analysis and remediation of social injustice. My springboard for this argument is a debate – principally represented here between Tommie Shelby and Elizabeth Anderson, but with much deeper historical roots and many flowering branches – about whether racial‐justice advocacy should prioritise integration (bringing different groups together) or community development (building wealth and political power within the black community). Although I incline toward something closer to Shelby's 'egalitarian pluralist' approach over Anderson's single‐minded emphasis on integration, many of Shelby's criticisms of integrationism are misguided, and his handling of the empirical literature is profoundly unbalanced. In fact, while both Shelby and Anderson defend the importance of social science to their projects, I'll argue that each takes a decidedly unempirical approach, which ultimately obscures the full extent of our ignorance about what we can and ought to do going forward. A more authentically empirical tack would be more epistemically humble, more holistic, and less organised around what I'll call prematurely formulated 'Grand Unified Theories of Social Change'. I defend a more 'diversified experimentalist' approach, which rigorously tests an array of smaller‐scale interventions before trying to replicate and scale up the most promising results.